Gaya Kepemimpinan Kepala Desa Perempuan di Desa Watumanu Kecamatan Jerebuu Kabupaten Ngada - Valeriana Anu; Laurensius P. Sayrani; Yaherlof Foeh (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study aims to analyze the leadership style of female village heads in Watumanu Village in carrying out their duties and responsibilities in organizing village government. The main focus of this study is on aspects of leadership style that highlight four leadership indicators including decision making, motivation, communication, and supervision. The type of research used in this study is qualitative research with a descriptive approach. The results of the study indicate that the head of Watumanu Village uses a feminine-masculine leadership style and a transactional-transactional leadership style flexibly according to the situation. This was obtained by analyzing four aspects of leadership style including decision making, motivation, communication, and supervision. In the aspects of decision making and communication, the head of Watumanu Village uses a balanced leadership style between feminine and masculine characters. While in the aspect of motivation, the village head uses a feminine-transformational leadership style. The feminine-transactional leadership style is applied by the head of Watumanu Village in the aspect of supervision to improve the performance of village officials.